Analysis of mechanism of Nafion® conductivity change due to hot pressing treatment. (April 2016) - DeBonis, D.; Mayer, M.; Omosebi, A.; Besser, R.S.
Abstract: In previous work, the authors observed that multiple hot-pressing cycles of Nafion 212 prior to Proton Exchange Membrane Fuel Cell (PEMFC) operation was found to result in significant performance gains. In order to further explore this effect, Nafion 212 samples were subjected to various thermal treatments and then to various analytical techniques in order to probe whether changes to the membrane contributed to these performance gains in a substantial way. Electrochemical Impedance Spectroscopy (EIS) measurement sought to validate that the treatment caused a proton conductivity change. Thermogravimetric Analysis (TGA) and Fourier Transform Infrared Spectroscopy (FTIR) measurements were implemented to determine whether chemical changes in the membrane occurred. Results suggest that the hot pressing treatment causes a significant effect in the electrical properties of Nafion 212, however the physical change that occurs in the polymer is not chemical in nature. Further analysis attempts to support the idea that the change in proton conductivity is due to water channel reconfiguration in the membrane, activated by elevated temperature and compressive stress at the glass transition temperature of the Nafion 212. Highlights: Extended hot-pressing cycles do not lead to water content changes in rehydrated Nafion 212 membranes. FTIR indicates no substantial chemical change to Nafion 212 membranes after hot-pressing. Conductivity of Nafion 212 becomes anisotropic (in-plane > through-plane by over 30%) after extended hot-pressing. PEMFC performance increase after hot-pressing does not correlate substantially with changes to membrane properties. EIS supports the notion that hot-pressing leads to improved ORR activation and/or improved cathode transport kinetics.